Abstract

No abstract available.

Full Article  |  PDF Article

References

  • View by:
  • |
  • |

  1. J. W. Goodman, Introduction to Fourier Optics (McGraw–Hill, New York, 1968), pp. 90–97.

Goodman, J. W.

J. W. Goodman, Introduction to Fourier Optics (McGraw–Hill, New York, 1968), pp. 90–97.

Other (1)

J. W. Goodman, Introduction to Fourier Optics (McGraw–Hill, New York, 1968), pp. 90–97.

Cited By

OSA participates in Crossref's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Alert me when this article is cited.


Figures (6)

Fig. 1
Fig. 1

Coherent imaging system, object illuminated by collimated light.

Fig. 2
Fig. 2

Coherent imaging system, object illuminated by converging light.

Fig. 3
Fig. 3

Digitally computed image irradiance distribution for collimated illumination.

Fig. 4
Fig. 4

Experimentally observed image irradiance distribution for collimated illumination.

Fig. 5
Fig. 5

Digitally computed image irradiance distribution for converging illumination.

Fig. 6
Fig. 6

Experimentally observed image irradiance distribution for converging illumination.

Equations (16)

Equations on this page are rendered with MathJax. Learn more.

h ( x i , x 0 ) = 1 λ ( d i d 0 ) 1 2 exp [ j π x i 2 λ d i ] exp [ j π x 0 2 λ d i ] · - P ( x ) exp [ - j 2 π λ ( x i d i + x 0 d 0 ) x ] d x .
A i ( x i ) = - h ( x i , x 0 ) A 0 ( x 0 ) d x 0 .
A i ( x i ) = l λ ( d i d 0 ) 1 2 exp [ j π x i 2 λ d i ] - exp [ j π x 0 2 λ d 0 ] · sinc [ l ( x i λ d i + x 0 λ d 0 ) ] A 0 ( x 0 ) d x 0 ,
x ˜ i x i M l ,             x ˜ 0 - x 0 l ,             M d i d 0 ,             s l 2 λ d 0 ,
A i ( x ˜ i ) = s M exp ( j π M s x ˜ i 2 ) - exp ( j π s x ˜ 0 2 ) · sinc [ s ( x ˜ i - x ˜ 0 ) ] A 0 ( x ˜ 0 ) d x ˜ 0 .
exp ( j π s x ˜ 0 2 ) exp ( j π s x ˜ i 2 ) .
A i ( x ˜ i ) = s M - sinc [ s ( x ˜ i - x ˜ 0 ) ] A 0 ( x ˜ 0 ) d x ˜ 0 ,
H ( ν ) = rect ( ν / s ) .
π s [ x ˜ 0 + W ( x ˜ 0 ) ] 2 - π s x ˜ 0 2 = π
W ( x ˜ 0 ) = ( x ˜ 0 2 + 1 / s ) 1 2 - x ˜ 0 .
W ( x ˜ 0 ) = ( x ˜ 0 2 + 1 / s ) 1 2 - x ˜ 0 ( 1 / s ) .
( 1 / s ) 1 2 ( 1 / s )
( l 2 / λ d 0 ) 1.
W ( x ˜ 0 ) ( 1 / 2 x ˜ 0 s ) ( 1 / s )
x ˜ 0 1 2 ,             x 0 ( l / 2 ) .
x 0 ( l / 8 ) ,